KAJIAN PEMASARAN IKAN LEMURU (Sardinella Lemuru) DI MUNCAR – BANYUWANGI - Kusmiati, Ati (Jurnal Sosial Ekonomi Pertanian, 2007)
The aim of this research is to analyze lemuru fish marketing in Muncar – Banyuwangi Regency through marketing margin analysis during peak season and lean season. Research location was selected purposively. Method of analysis were descriptive and analytic. Snow ball sampling was used in this research. Both primary and secondary data were collected in this study. Results show that the shorter the marketing chains the smaller marketing margin. Marketing margin during peak season was smaller compared than marketing margin during the lean season, because during the lean season, consumers were unable to get lemuru easily. So, lemuru price become higher. Although the lemuru price was high, consumers still sought to buy it. Therefore, share received by fisherman is higher during the peak season. Key word: marketing margin, peak season and lean season.